Deteksi dan Pencegahan Serangan Remote Code Execution Terhadap Wing FTP Web Server - Triwibowo, Muhammad; , Helman Muhammad, S.T., M.T (2015)
A network security issues extremely vulnerable to attacks from all sides. The reason of the attack of course vary. Among the reasons for the damage, revenge, political, or Just fun - fun only to the performance capabilities. Behind the ease of accessing information provided by the internet there is a great danger that is lurking, namely the various kinds of attacks that tried to find a gap of computer network security system being used. The attacks can cause data loss and even damage to hardware. This study will identify how an attack Remote Code Execution work against Wing File Transfer Protocol (FTP Wing Web Server), and then make the detection of attacks using snort. Detection and prevention is done by the draft makes an active firewall to identify each incoming data into the server, whether the data is the Remote Code Execution attack or not. Results from this study is a network security system that can detect and prevent attacks trerjadinya Remote Code Execution against Wing FTP Web Server. System generated in this study can be seen through the testing of the system, in this case includes two stages, namely stage attack detection and prevention of the attack phase.